Toxic effects of chromium on the aquatic cyanobacterium Oscillatoria sp and removal of chromium by biosorption - Jayashree, S; Thangaraju, N; Gnanadoss, J Joel (Journal of Experimental Sciences, 2012)
“Chromium” is a non-essential metal for microorganisms and plants and a serious pollutant in diverse environment conditions. The hexavalent form of the metal Cr (IV) is considered to be more toxic than relatively harmless Cr(III) form. Certain microorganisms in the environment are able to tolerate high levels of Cr due to their resistance mechanism. In the present work we report the toxic effect of chromium on Oscillatoria sp and the removal of hexavalent using the cyanobacterium Oscillatoria sp., by biosorption method. Oscillatoria sp., was grown in BG-11 medium containing different concentration of Cr. Effect of Cr on cellular metabolism was studied by estimating the amount of chlorophyll a, carotenoids, c. phycocyanin, allophycocyanin, sugars, free amino acids and proteins at various metal concentration. An increase in metal concentration caused a decrease in the growth of the Oscillatoria sp., and also decreased the cellular contents like chlorophyll a, carotenoids, c.phycocyanin, allophycocyanin, sugars, free amino acids and proteins. Biosorption of chromium by Oscillatoria sp., was carried out using living cells, heat killed cells and pre-treated cells. Results showed that high amount of metal were adsorbed by heat killed and living cells of Oscillatoria sp. The experimental conditions used in the present work are simple and have low operational cost. The proposed biosorption method is economically feasible and eco-friendly in nature.